Perbedaan Asupan Energi, Protein, Zink, dan Perkembangan pada Balita Stunting dan non Stunting - Farahiyah Yusni Adani; Triska Susila Nindya (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Stunting is a nutritional problem caused by inadequate nutrition intake for a long time and/or recurrent infectious diseases. The impacts of stunting are increase mortality, morbidity, health costs, decrease cognitive development, motor, and language development.There are nutrients that important to linear growth as energy, protein, and zinc. Objectives: The purpose of this study was to analyze the differences of intake of the energy, protein, Zinc, development in stunting and non-stunting toddler. Methods: The research was a cross sectional study with quantitative approach. The sample size was 64 toddler in Manyar Sabrangan Sub-district, Surabaya, 32 toddler each stunting and non-stunting were taken by simple random sampling. The data were collected by measuring height, structure questionnaire, food recall 2x24 hours, questionnaire for screening development (KPSP). The data were analyzed using Chi Square Test. Results: Non-stunting toddlers have an adequate intake of energy, protein, zinc respectively 71,9%, 93,7%, 71,9%, meanwhile appropriate development was 75%. Stunting toddlers have an inadequate intake of energy, zinc respectively 68,7%, 65,6% and adequate intake of protein was 68,7%, meanwhile deviance development was 62,5%. The results of this study showed that the comparison of differences between stunting and non-stunting toddler were significant (≤0,05) in energy, protein, Zinc, and development. Conclusion: Non-stunting toddler have a higher intake of the energy, protein, Zinc, and development rather than stunting toddler. Mother of toddler should to increase intake of energy, protein, Zinc to prevent stunting and achieve appropriate development.ABSTRAK Latar belakang: Stunting adalah permasalahan gizi yang disebabkan oleh asupan zat gizi yang kurang dalam waktu lama dan/atau penyakit infeksi yang berulang. Terdapat beberapa zat gizi yang berperan dalam pertumbuhan linier. Salah satu zat gizi tersebut adalah energi, protein, dan zink. Dampak stunting dapat meningkatkan mortalitas, morbiditas, biaya kesehatan, menurunkan perkembangan kognitif, motorik, dan bahasa.Tujuan: Tujuan dari penelitian ini adalah untuk menganalisis perbedaan asupan energi, protein, Zink, dan perkembangan pada balita stunting dan non stunting.Metode: Penelian ini menggunakan studi cross sectional dengan pendekatan kuantitatif. Sampel terdiri dari 64 balita yang di Kelurahan Manyar Sabrangan Surabaya, balita stunting dan non-stunting masing-masing berjumlah 32. Pengumpulan data menggunakan pengukuran tinggi badan, food recall 2x24 jam, kuesioner pra skrining perkembangan (KPSP) ,dan kuesioner. Data dianalisis menggunakan chi square Tets.Hasil: Balita non-stunting mempunyai asupan energi, protein, zink adekuat yaitu 71,9%, 93,7%, dan 71,9% serta perkembangan sesuai yaitu 75%. Balita stunting mempunyai asupan energi, zink inadekuat yaitu 68,7%, 65,6% dan protein adekuat yaitu 68,7% serta perkembangan menyimpang yaitu 62,5%. Hasil dari penelitian menunjukkan perbandingan balita stunting dan non stunting adalah ada perbedaan signifikan (p≤0,05) pada energi, protein, Zink, dan perkembangan.Kesimpulan: Balita non-stunting mempunyai asupan energi, protein, Fe, Zink yang tinggi dan stimulasi psikososial serta perkembangan yang baik daripada balita stunting. Ibu balita harus meningkatkan asupan energi, protein, Zink agar dapat mencegah terjadinya stunting dan dapat mencapai perkembangan yang sesuai.